The Impact of Teacher Training Using Mobile Augmented Reality Games on Their Professional Development - Margarida M. Marques; Lúcia Pombo (MDPI AG, 2021)
Ongoing technology progress sustains innovative teaching approaches. Mobile devices, augmented reality (AR), and games are a few of the new resources that teachers have at their disposal to promote student learning. However, their effective integration into practices requires training, so there is a need to analyze the impact of training initiatives on teacher professional development. A case study is being conducted on the development process of mobile AR games for Science, Technology, Engineering and Mathematics (STEM) learning by 14 Portuguese in-service teachers in a 50 h workshop. This contribution refers to the analysis of this training's impact on teacher professional development through a questionnaire filled in at the beginning and end of the workshop. This study registered a higher impact on teachers' understanding of AR educative use, the less-known approach, compared to mobile and game-based learning. Moreover, teachers became more experienced with these approaches as learners, and reported having explored them with their students during the workshop period. Teacher ability to identify benefits and barriers in these approaches increased with the workshop, particularly the learning that could be promoted with mobile AR games. The presented set of barriers to implementation is relevant to future teacher professional-development initiatives.